2013
DOI: 10.1189/jlb.0912433
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines activate blood leukocytes via trace amine-associated receptors TAAR1 and TAAR2

Abstract: Certain biogenic amines, such as 2-PEA, TYR, or T1AM, modulate blood pressure, cardiac function, brain monoaminergic systems, and olfaction-guided behavior by specifically interacting with members of a group of rhodopsin-like receptors, TAAR. A receptor that is absent from olfactory epithelia but had long been identified in the brain and a variety of peripheral tissues, TAAR1 has been found recently in blood B cells, suggesting a functional role of TAAR1 in these cells. With the present study, we have set out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
158
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(171 citation statements)
references
References 41 publications
7
158
0
6
Order By: Relevance
“…This has subsequently been verified by numerous laboratories (Mühlhaus et al, 2014;Cöster et al, 2015;Chiellini et al, 2017), with 3IT also shown to act as an agonist at TAAR2 (Babusyte et al, 2013;Cichero and Tonelli, 2017) and as an inverse agonist at TAAR5 (Dinter et al, 2015c). 3IT is promiscuous, however, and also interacts with high affinity at a 2 -adrenoceptors (Regard et al, 2007;Dinter et al, 2015b), b-adrenergic receptors (Meyer and Hesch, 1983;Kleinau et al, 2011;Dinter et al, 2015a), muscarinic acetylcholine receptors (Laurino et al, 2016), transient receptor potential cation channel subfamily M member 8 ion channels (Khajavi et al, 2015;Lucius et al, 2016), various monoamine and organic anion transporters (Snead et al, 2007;Panas et al, 2010), and molecular target(s) within mitochondria, including the F 1 -F 0 ATP synthase (Cumero et al, 2012) and possibly complex III (Venditti et al, 2011).…”
Section: E 3-iodothyronaminementioning
confidence: 66%
See 4 more Smart Citations
“…This has subsequently been verified by numerous laboratories (Mühlhaus et al, 2014;Cöster et al, 2015;Chiellini et al, 2017), with 3IT also shown to act as an agonist at TAAR2 (Babusyte et al, 2013;Cichero and Tonelli, 2017) and as an inverse agonist at TAAR5 (Dinter et al, 2015c). 3IT is promiscuous, however, and also interacts with high affinity at a 2 -adrenoceptors (Regard et al, 2007;Dinter et al, 2015b), b-adrenergic receptors (Meyer and Hesch, 1983;Kleinau et al, 2011;Dinter et al, 2015a), muscarinic acetylcholine receptors (Laurino et al, 2016), transient receptor potential cation channel subfamily M member 8 ion channels (Khajavi et al, 2015;Lucius et al, 2016), various monoamine and organic anion transporters (Snead et al, 2007;Panas et al, 2010), and molecular target(s) within mitochondria, including the F 1 -F 0 ATP synthase (Cumero et al, 2012) and possibly complex III (Venditti et al, 2011).…”
Section: E 3-iodothyronaminementioning
confidence: 66%
“…As previously noted, PEA and TYR may be released from activated platelets (D'Andrea et al, 2003) and have been reported to be positive chemotactic agents for leukocytes (Babusyte et al, 2013). The joint regulation of TAAR1 and TAAR2 is important from this aspect, as the chemoattractant response of leukocytes toward TAAR1-selective agonists appears to be dependent on the presence of both TAAR1 and TAAR2, possibly due to the need for heterodimerization of the two (Babusyte et al, 2013). From this perspective, the TAAR1/TAAR2 axis may provide a molecular explanation for the well known immune dysfunction that is associated with amphetamine-like drugs of abuse (Boyle and Connor, 2010;Sriram et al, 2015), many of which are TAAR1 agonists.…”
Section: Effects In the Peripherymentioning
confidence: 71%
See 3 more Smart Citations